The Rate and Risk Factors of Postpartum Depression in Vietnam From 2010 to 2020: A Literature Review - Nguyen, Huong Thi Thanh; Hoang, Anh Phuong; Do, Ly Thi Kim; Schiffer, Stephen; Nguyen, Huyen Thi Hoa (Frontiers in Psychology, 2021)
Postpartum depression (PPD) is commonly seen in women after birth and can lead to adverse effects on both the mothers’ health and child(ren) development. In Vietnam, there have been a number of studies examining the rate and risk factors of PPD, but none has provided a systematic review. This current literature review aims to summarize and synthesize the current state of knowledge of studies conducted in Vietnam to provide a comprehensive understanding of the postpartum depression phenomena during the last ten years. Data sources: A literature search was conducted relying on the most common online databases – MEDLINE/PubMed, ScienceDirect, and Google Scholar, that included articles if they (i) examined prevalence or risk factors of PPD; (ii) were conducted among Vietnamese participants using either quantitative, qualitative, or mixed-method and (iii) were published from 2010 to 2020. After the filtering process, 18 articles were eligible to be reviewed. Results: Research in Vietnam on PPD are conducted among women at and after 1-month delivery. The rate of PPD reported in Vietnam among mothers at postnatal time points from 1 to 12 months ranged from 8.2% to 48.1%. Risk factors can be clustered into three groups: personal factors, family factors, and environmental factors. Recommendation: Further research should focus on examining PPD at an earlier stage within the first month after birth. The investigation of risk factors in a comprehensive manner for Vietnamese mothers would also be recommended.